Prenatal Intervention for Lower Urinary Tract Obstruction - David M. Kitchens; C. D. Anthony Herndon (The Scientific World Journal)
Hydronephrosis is one of the most common abnormalities detected on routine prenatal ultrasounds, being noted in up to 1% of fetuses. Rarely, severe hydronephrosis coexists with oligohydramnios, which portends a poor prognosis. We review the most recent literature on the results of prenatal intervention in this setting. Presently, the first randomized controlled trial to address whether prenatal vesicoamniotic shunting improves survival and renal function is underway, and should address the value of prenatal intervention.